The Great Reset: The Implementation of Sustainable Development in Economy Post Covid-19 - Alviola Taraditha Asmarani; Said Rivaldi Assagaf; Raffyanda Muhammad Indrajaya; Kevin Thedeus; Fitria Rachmawati (Ilomata International Journal of Social Science, 2023)
The COVID-19 Pandemic has forced prevention efforts to be implemented by the countries worldwide. Some countries have succeeded with the efforts, whereas others are still struggling, thus it triggered an economic reset to be experienced by the affected countries. Nevertheless, with the increasing global warming and ecological damage, the economic reset caused by the COVID-19 pandemic becomes an opportunity for countries to cope with the structural challenges of the economy in order to create a sustainable development system and to prevent further destruction of nature on a global level. This article aims to explore how the economic downturn caused by the COVID-19 pandemic can function as a tool and basis from which a more sustainable economic system can be implemented.